Intensive nitrogen fixation associated with anaerobic decomposition of horticultural wastes - Ong, Ying Yu. (2009)
Nitrogen is an important element for growth in all living organism, however it must be reduced before it can be utilized. This process is performed exclusively by diazotrophs through its nitrogenase enzyme until synthetic fertilizers come about. Agriculture requires large amount of fertilizers yearly to meet increasing global demand. However as natural gas becomes scarce, price of synthetic nitrogen fertilizers increased drastically because the process was energy intensive. Therefore, alternative fertilizers production through biological nitrogen fixation was studied. The objective was to use horticultural waste as energy source for nitrogen fixation to take place and the final goal was to produce a continuous reactor for intensive nitrogen fixation. The conditions required for this purpose were studied through 2 batch tests. Sawdust and leaf litter were used as carbon source and inoculum produced using soil provided bacteria for N fixing and cellulose degradation. Results gathered from the tests are presented. Nitrogen fixation using sawdust occurred but at low levels (19.2 ± 2.4 mg/L) with a yield of 1.1 mg N / g of carbon substrate decomposed. This was attributed to bad substrate quality. Finally, it is recommended that another type of horticultural waste to be used and the types of horticultural waste in Singapore to be studied.